FIRST EXPERIENCE OF PROGRAMMING A COURT DECISION (Russian Journal of Economics and Law, 2017)
Objective: Consideration of the computer program model for making a lawful and well-grounded judicial act in order to reduce the times for making the court decision.Methods: universal dialectic-materialistic method, which removes the contradictions of the professional training of judges and procedural controls; the formal legal method for transferring the requirements of the law and jurisprudence for the law-enforcement activity into programs for judges and case participants; the object-oriented modeling; object-oriented programming methodology. Results: a computer program was created that allows to adjudicate in a civil case if the claim is recognized by the defendant. The program does not resolve the judge from the decision-making process, but creates conditions to move along the stages of law-enforcement procedure and legal reasoning in accordance with the requirements of the law and of legal science. Therefore, filling forms manually in the trial should be simultaneous with writing the decision (judgment, sentence, assessment). The program includes the following sections: preparation of forms common to certain types of proceedings, certain categories of cases, courts; in the above forms, determination of the order to establish the actual circumstances, the burden of proof distribution, types of evidence, methods of law interpretation, characteristics of collisions and gaps in legislation and ways to overcome them; the standard wording in the judicial act templates and in the forms; mandatory and optional information in the form. Based on the above, the article concludes that, by analogy with the presented program, it is possible to create software for making a lawful, well-grounded and fair judicial act for other categories of cases and, as a consequence, to reduce the period of making judicial decisions. Scientific novelty: the first computer program is created for rendering and production of judicial decisions.Practical significance: the model is made to create a mass tool of judicial activity, to eliminate errors and clearly unjust ruling in the court proceedings, as well as to reduce the production time of the judgement.